A Metamorphic Study of Pretoria Group Sediments Found at the Dwarsrivier Pass, Bushveld Igneous Complex, South Africa - Roberts, R.J. (James) (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2019.